Chapter MEMS Technologies Enabling the Future Wafer Test Systems - Tunaboylu, Bahadir (InTechOpen, 2018)
As the form factor of microelectronic systems and chips are continuing to shrink, the demand for increased connectivity and functionality shows an unabated rising trend. This is driving the evolution of technologies that requires 3D approaches for the integration of devices and system design. The 3D technology allows higher packing densities as well as shorter chip-to-chip interconnects. Micro-bump technology with through-silicon vias (TSVs) and advances in flip chip technology enable the development and manufacturing of devices at bump pitch of 14 μm or less. Silicon carrier or interposer enabling 3D chip stacking between the chip and the carrier used in packaging may also offer probing solutions by providing a bonding platform or intermediate board for a substrate or a component probe card assembly. Standard vertical probing technologies use microfabrication technologies for probes, templates and substrate-ceramic packages. Fine pitches, below 50 μm bump pitch, pose enormous challenges and microelectromechanical system (MEMS) processes are finding applications in producing springs, probes, carrier or substrate structures. In this chapter, we explore the application of MEMS-based technologies on manufacturing of advanced probe cards for probing dies with various new pad or bump structures.